Step-by-step explanation:
- We must first add up the ratios:5+12+2+15+29 = 63, this will be the total ratio the money was shared
- Then we pick out the ratio for each family accordingly:
For the first family, 5 out of the total ratio = 5/63
For the second family, 12 out of the total ratio = 12/63
For the third family, 2 out of the total ratio = 15/63
For the fifth family, 29 out of the total ratio = 29/63
a) The first family = 5/63 of the money, $630
we can therefore say the money they received is
= 5/63 ×630
= $50
b) The last family = fifth family = 29/63 of the money, 630
= 29/63 × 630
= $290
recall that the first family received $50 , the positive difference between the money received by both the first and last family
= $290 - $50
= $240
c) Since another family joins in, the total number of families become 6
- the money the received is n
we can't find the average without knowing what the second, third, and fourth family received out of that money
the second family = 12/63 ×630
= $120
the third family = 2/63 × 630
= $20
the fourth family = 15/63 × 630
= $150
- Average generally is = total sum/ frequency or number of occurrences or people
in this case, we were told the average became $140
which means that
sum of money received by the families/ the number of families involved in the sharing = $140
<h3>
( $50+$120+$20+$150+$290+n)/6 = $140</h3>
($630+n)/6= $140
now the plan would be to make n subject of formula
- multiply both sides of the equation by 6, the equation will become
$630+n = $840
take $630 to the other side, it becomes -$630
n = $840-$630
n = $210
therefore the newly added family received $210
I honestly hope I explained it properly...thank you